Towards a redefinition on the role of library student assistants in the provision of library service - Humarang, Lora C.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The UP Diliman libraries serve a wide variety of clients including UP students, UP faculty, UP employees and other outside researchers. In order to accommodate this large number of clients, the administration set up a Library Student Assistantship Program which will hopefully ensure an effective and efficient library service. Although Library Student Assistants in the provision of library service is still indefinite. So, what exactly is the role of Library Student Assistants in the provision of Library Service?
This study is an investigation reaching towards redefining the role of Library Student Assistants through a thorough exploration of their tasks. Of the 102 population (70 LSA and 32 LS), 89 respondents (62 LSA and 27 LS) responded. It was determined that the Library Student Assistants' role in the provision of library service is the performance of non-professional yet essential tasks in the library. These non-professional tasks include shelving, answering the phone, locating materials, shelf-reading, encoding, typing, etc.
This role continues to evolve because the role of LSA is also susceptible to change due to outside factors such as technology, library clients, library resources, course, type of library and administrative policies.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Student library assistants -- Philippines -- Quezon City